Transformative-Participatory Legal Research Method for Harmonizing The Existence of The Living Law in Indonesia - Halim, Yoefanca; Sudewo, Fricky; Justian, Jestin (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2019)
The most common research which conducted in Indonesia is a doctrinal research, based on the deductive approach. Theoretically, all provisions have noble goals, but in practice there are several difficulties in term of implementation, especially related to existence of living law. Therefore, appropriate legal-research method is needed to counter the polemic, namely the use of transformative-participatory legal research method. The article aims to explore how to harmonize the living law with transformative-participatory legal research methods. The method uses in the study is the normative legal research method. The research found that through the transformative-participatory legal research, legal researchers would still accommodate the essence of legal analysis founded in conventional methods, but it will not be confined by those methods. Â The living law is the essence in society and based on transformative-participatory research method, the law-making process needs a community participation and empowerment.